Polymeric Microneedles: An Emerging Paradigm for Advanced Biomedical Applications - Deepak Kulkarni; Dipak Gadade; Nutan Chapaitkar; Santosh Shelke; Sanjay Pekamwar; Rushikesh Aher; Ankita Ahire; Manjusha Avhale; Rupali Badgule; Radhika Bansode; Bhujang Bobade (MDPI AG, 2023)
Microneedles are gaining popularity as a new paradigm in the area of transdermal drug delivery for biomedical and healthcare applications. Efficient drug delivery with minimal invasion is the prime advantage of microneedles. The concept of the microneedle array provides an extensive surface area for efficient drug delivery. Various types of inorganics (silicon, ceramic, metal, etc.) and polymeric materials are used for the fabrication of microneedles. The polymeric microneedles have various advantages over other microneedles fabricated using inorganic material, such as biocompatibility, biodegradation, and non-toxicity. The wide variety of polymers used in microneedle fabrication can provide a broad scope for drug delivery and other biomedical applications. Multiple metallic and polymeric microneedles can be functionalized by polymer coatings for various biomedical applications. The fabrication of polymeric microneedles is shifting from conventional to advanced 3D and 4D printing technology. The multifaceted biomedical applications of polymeric microneedles include drug delivery, vaccine delivery, biosensing, and diagnostic applications. Here, we provide the overview of the current and advanced information on polymers used for fabrication, the selection criteria for polymers, biomedical applications, and the regulatory perspective of polymer-based and polymer-coated microneedles, along with a patent scenario.